Knowledge-intensive services and competitiveness of the forest cluster: Case Finland - Esa Viitamo (The Research Institute of the Finnish Economy (ETLA), 2003)
New technologies in the globalized business environment are shaping competitive strategies in unprecedented ways. As important as the race for developing more advanced ICT products is the ability to convert these advances into a higher productivity of the assets in other economic activities. This holds true also for the business services, which assume a major role in the ongoing industrial restructuring, and as a source of competitiveness. Given these stylized facts this report examines the relations between services, manufacturing, technological progress and organizational factors, which generate competitiveness in industrial clusters. Among manufacturing sectors the forest industry is used here as a special case. Much of the existing literature concentrates on the competitiveness impacts of ICT investments made by the manufacturing sector. Our arguments is that even a higher potential can be found in a specific indirect effect, that is, the ICT-based services used as production inputs. The realization of the potential depends on the governance of service transactions. Any attempt to characterize the changing role of services should also recognize the changing contents of services – or the way they are produced and provided. Technological changes and new forms of competition are forging our understanding of the very nature of economic activities and the factors differentiating industries. While the progress towards service economy is taking place, there are various ways to interpret the change.
Keywords: 330; service activity; forest industry; competitiveness; ICT; Forstwirtschaft; Wettbewerb; Informationstechnik; Finnland